The effect of induction chemotherapy followed by chemoradiotherapy in advanced head and neck cancer: a prospective study - Nikam, Bhushan M.; Singh, Kailash K.; Kharde, Rohan; Nagshet, Siddharth; Borade, Dipalee; Moosa, Zaiba (International Journal of Research in Medical Sciences, 2017)
Background:Objective of current study was to observe the local control, progression free survival and organ preservation for locally advanced head and neck cancer by using induction Chemotherapy followed by concurrent chemoradiotherapy. Methods:102 patients enrolled in this study with stage III-IVB of head & neck cancer. Patients were assessed and treated by faculty of the department as per NCCN guidelines. Group A patients received three courses of cisplatin (100mg/m2) and paclitaxel (175mg/m2) at every 21 days interval followed by concurrent chemoradiothearpy with cisplatin 30mg/m2 on weekly basis while group B received only concurrent chemoradiothearpy. Radiotherapy consisted of total dose up to 66-70 Gy. by conventional fractionation schedule. Results:From August 2011 to July 2013, total 102 patients have completed 14 months of follow up after completing definitive treatment group A : 48 and group B: 54 patients. Response evaluation was done after one and half months of completion of chemoradiotherapy in both arms. Complete response rate was 60.42% and 38.88 % in study and control arm respectively while partial response was 72.92% and 55.56%. Most common grade III or IV toxicity was mucositis in group A and skin reaction in control arm. At a median follow-up 13 months the median progression free survival in group A was 11.5 months and 9 months in group B. Conclusion: Response to induction chemotherapy was useful as predictive factor for ultimate outcome and progression free survival. But our study shows statistically significant improvement in complete response rate in group A as compared to group B (p<0.05). Our induction chemotherapy with two-drug regimen followed by concurrent chemoradiotherapy was well tolerated with manageable toxicity and good locoregional control.